2017
DOI: 10.1371/journal.pone.0178743
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of suicide attempts in left-behind children and non-left-behind children in rural China

Abstract: To estimate the prevalence of suicide attempts and explore the shared and unique factors influencing suicide risk in left-behind children (LBC) and non-left-behind children (NLBC) in rural China, this study collected data using a multi-stage cluster random sampling method from 13,952 children including 6,034 LBC and 7,918 NLBC. Sociodemographic characteristics, suicide attempts, neglect and physical abuse, negative life events, and loneliness were measured by self-reported questionnaires. Data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…Studies129, 133 reporting anxiety outcomes similarly found increased risks among left-behind children and adolescents compared with children of non-migrants. Consistent with our findings, a large study of adolescents in China (n=13 952) found a significant increase in suicide attempts in left-behind adolescents compared with adolescents who were not left behind (3·75% vs 2·86%, p<0·01) 134 . Two studies135, 136 assessed nutrition outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Studies129, 133 reporting anxiety outcomes similarly found increased risks among left-behind children and adolescents compared with children of non-migrants. Consistent with our findings, a large study of adolescents in China (n=13 952) found a significant increase in suicide attempts in left-behind adolescents compared with adolescents who were not left behind (3·75% vs 2·86%, p<0·01) 134 . Two studies135, 136 assessed nutrition outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Although millions of migrant parents pursue better opportunities for their children, their children left behind actually live in a situation lacking parental care and nurturance and are more likely to suffer abuse than others ( Zhao, Liu & Wang, 2015 ). LBC were more likely to report being bullied ( Otake, Liu & Luo, 2017 ), and suicide attempts ( Chang et al, 2017 ) than non-LBC did in China.…”
Section: Introductionmentioning
confidence: 98%
“…A chronic and painful state of loneliness is harmful to mental and physical health (Heinrich and Gullone, 2006; Qualter et al, 2015; Lempinen et al, 2018); in fact, it may elevate the risk for depression (Cacioppo et al, 2015), mortality (Holt-Lunstad et al, 2015), social withdrawal, and suicidality (Schinka et al, 2013), even damaging the immune, cardiovascular, and nervous systems (Cacioppo et al, 2015; LeRoy et al, 2017). As for left-behind children, a sense of yearning for their parents and chronically high loneliness result in a constellation of mental problems, including conduct problems (Yu, 2017) and suicide attempts (Chang et al, 2017).…”
mentioning
confidence: 99%